(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
The present study aimed to evaluate the methanolic extract of Cordia dichotoma (MECD) leaves (MECD) for anxiolytic activity in rats. Elevated plus maze test (EPM) and light and dark test were used to evaluate the antianxiety property of MECD. Diazepam (2 mg/kg) and methanolic extract of Cordia dichotoma (50,100, and 200n mg/Kg, p.o.) were administered daily for 21 days. EPM and light and dark tests were assessed on the 7th, 14th, and 21st days. On the 21st day, animals were killed, and the striatum was excised for the estimation of various biochemical parameters like malondialdehyde (MDA), glutathione (GSH), superoxide dismutase (SOD), catalase (CAT) as well as histopathological study. In this study, the (MECD) demonstrated a significant and dose-dependent increase in time spent in the open arm of the elevated plus maze (EPM) test and the time spent in the light compartment in the light & dark test. It also significantly decreased the MDA level and increased CAT, GSH, and SOD levels (p < 0.001) in the MECD-treated group compared to the control group. Furthermore, MECD significantly restored histological abnormalities, revealing reduced stress-induced damage. It is suggested that MECD possessed an anxiolytic effect via modulation of endogenous enzymes in experimental-induced anxiety in rats.